Insulin Modulation of Magnetoencephalographic Resting State Dynamics in Lean and Obese Subjects - Stingl, Krunoslav T.; Kullmann, Stephanie; Guthoff, Martina; Heni, Martin; Fritsche, Andreas; Preissl, Hubert (Frontiers in Systems Neuroscience, 2010)
Lean and obese subjects can exhibit differences in neuronal activity during resting state and tasks. Changes in hormonal status and their action related to increased body weight may be the determining factor for these differences. One prime candidate is insulin, which until recently, was mainly related to its metabolic function for the transport and regulation of glucose in the periphery. However insulin also acts as an anorexic signal in the central nervous system (CNS) contributing to the termination of food-intake in the postprandial state. In our study, we examined with whole head magnetoencephalography (MEG) effect of intranasal insulin on the dynamics of the resting state network in a placebo controlled study. Weighted clustering coefficient C, which describes local interconnectedness, and weighted path length L, a measure of global interconnectedness, were computed. These parameters showed high intraindividual reliability. However, no difference for the network dynamics was found between lean and obese subjects in the basal state. The application of insulin led to subject specific changes and we found a statistically significant positive correlation between the insulin induced change in path length in the theta band (4-8 Hz) and body mass index. The change in pathway length after insulin administration indicates a strong insulin modulation on global communication efficiency, which is probably related to the signaling between different regions involved in satiation and homeostatic control.